Interleaving as Cultural Technique in the Audio CD and the End of Archaeophonography - Eamonn Bell (Media Theory)
This article discusses a significant if imperceptible feature of how audio compact discs (CDs) inscribe sound: interleaving. It shows how CDs materialize interleaving—the microtemporal re-ordering of data—as a cultural technique of contemporary digital media, and, as such, how the CD’s surface testifies to much more general operations of cultural data processing than those that appear to be at stake in the few media-theoretical discussions of the format to date. First, I provide a brief overview of the CD’s operating principles, followed by a closer examination of the error-correction and detection system used in CD media. I explain how interleaving co-operates with this system to improve the resilience of disc media to both pre-sale defect and post-sale damage. I interpret this tacit and little-remarked-upon operation of CD players in cultural-technical terms. The perplexities of digital sound media push the principles of contemporary sound reproduction well beyond the kind of efficient and effective critical scrutiny we may associate with what I here call archaeophonographic sound media (for example, tape and vinyl LPs), unless we are willing to confidently assert the value of the media-technical explanatory register to digital media history.